Circuits regulating pleasure and happiness: evolution and role in mental disorders*. Issue 1 (5th May 2017) - Loonen, Anton J.M.; Ivanova, Svetlana A.
Abstract : Taking the evolutionary development of the forebrain as a starting point, the authors developed a biological framework for the subcortical regulation of human emotional behaviour which may offer an explanation for the pathogenesis of the principle symptoms of mental disorders. Appetitive-searching (reward-seeking) and distress-avoiding (misery-fleeing) behaviour are essential for all free-moving animals to stay alive and to have offspring. Even the oldest ocean-dwelling animal creatures, living about 560 million years ago and human ancestors, must therefore have been capable of generating these behaviours. Our earliest vertebrate ancestors, with a brain comparable with the modern lamprey, had a sophisticated extrapyramidal system generating and controlling all motions as well as a circuit including the habenula for the evaluation of the benefits of their actions. Almost the complete endbrain of the first land animals with a brain comparable with that of amphibians became assimilated into the human amygdaloid and hippocampal complex, whereas only a small part of the dorsal pallium and striatum developed into the ventral extrapyramidal circuits and the later insular cortex. The entire neocortex covering the hemispheres is of recent evolutionary origin, appearing first in early mammals. During the entire evolution of vertebrates, the habenular system was well conserved and maintained its function in regulating the intensity of reward-seeking (pleasure-related) and misery-fleeing (happiness-related) behaviour. The authors propose that the same is true in humans. Symptomatology of human mental disorders can be considered to result from maladaptation within a similar amygdalo/hippocampal–habenular–mesencephalic–ventral striatal system.